Mixotrophic trade‐off under warming and UVR in a marine and a freshwater alga. Issue 5 (25th May 2019) - González‐Olalla, Juan Manuel; Medina‐Sánchez, Juan Manuel; Carrillo, Presentación
Abstract : Mixotrophic protists combine phagotrophy and phototrophy within a single cell. Greater phagotrophic activity could reinforce the bypass of carbon (C) flux through the bacteria‐mixotroph link and thus lead to a more efficient transfer of C and other nutrients to the top of the trophic web. Determining how foreseeable changes in temperature and UVR affect mixotrophic trade‐offs in favor of one or the other nutritional strategy, along the mixotrophic gradient, is key to understanding the fate of carbon and mineral nutrients in the aquatic ecosystem. Our two main hypotheses were: (i) that increased warming and UVR will divert metabolism toward phagotrophy, and (ii) that the magnitude of this shift will vary according to the organism's position along the mixotrophic gradient. To test these hypotheses, we used two protists ( Isochrysis galbana and Chromulina sp.) located in different positions on the mixotrophic gradient, subjecting them to the action of temperature and of UVR and their interaction. Our results showed that the joint action of these two factors increased the primary production:bacterivory ratio and stoichiometric values (N:P ratio) close to Redfield's ratio. Therefore, temperature and UVR shifted the metabolism of both organisms toward greater phototrophy regardless of the original position of the organism on the mixotrophic gradient. Weaker phagotrophic activity could cause a less efficient transfer of C to the top of trophic webs.